Effect of Goji Berry (Lycium barbarum) Serum Extract on the Expression of Pro-Inflammatory Cytokines and Anti-Inflammatory Cytokines during Wound Healing in Wistar Rats: A Systematic Literature Review - Wisan, Angel Benny; Yasa, I Wayan Putu Sutirta; Wande, I Nyoman (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
Wound healing is a complex biological process involving the phases of hemostasis, inflammation, proliferation, and remodeling, in which cytokines and growth factors play an important role. This study aimed to evaluate the effect of administration of Goji Berry (Lycium barbarum) serum extract on the main molecular markers involved in wound healing in Wistar rats. This study was a systematic literature review that assessed the effect of administration of Goji Berry (Lycium barbarum) serum extract on the expression of mRNA pro-inflammatory cytokines (TNF and IL-1), anti-inflammatory cytokines (IL-10 and TGF-β), as well as matrix metalloproteinase enzyme MMP-9 and its inhibitor TIMP-1 in the wound healing process in Wistar rats. The findings of the review show that Goji Berry extract is able to suppress pro-inflammatory molecules while increasing anti-inflammatory molecules, thereby accelerating the transition from the inflammatory phase to the proliferative phase as well as supporting tissue regeneration. This extract also plays a role in regulating the degradation balance and repair of the extracellular matrix through increased expression of MMP-9 and TIMP-1, which ensures optimal tissue remodeling. Goji Berry extract has the potential to be an effective natural therapeutic agent in supporting wound healing with minimal side effects. Further research is needed to optimize doses, administration methods, and validate their application in humans for wider clinical use. This study highlights the potential of Goji Berry (Lycium barbarum) serum extract in modulating key molecular markers of wound healing. The results demonstrate the extract’s ability to balance pro- and anti-inflammatory mRNA expression and regulate extracellular matrix remodeling, thereby supporting faster and better tissue repair. These findings provide the basis for the development of effective natural wound therapies and guide further research into optimal clinical applications.